005 Delivering hospital care and services to children and young people with learning disabilities: the national picture. (December 2018) - Oulton, K; Carr, L; Jewitt, C; Kenten, C; Kerry, S; Hassiotis, A; Russell, J; Whiting, M; Tufrey-Wijne, I; Gibson, F
Abstract : A recent survey reports a decline in disabled children's services (https://disabledchildrenspartnership.org.uk/wp-content/uploads/2018/06/DCP-survey-report-June-2018.pdf). This presentation will focus on the organisational context in England for healthcare delivery in hospitals to children and young people with learning disabilities. We report staff perceptions of their ability to identify and meet the needs of these children and their families and provide high-quality hospital care. We also report on the extent of dedicated learning disability nurse provision in specialist children's hospitals. The views about the care of children and young people with learning disability were collated from an anonymised online survey (n=2261) and individual interviews (n=65) with hospital staff working with this population in 24 English hospitals. Within and across hospitals these data show that uncertainty and variation exist regarding what is currently available and accessed in terms of the organisational policies, systems and practices in place to support this patient group. Staff perceived this population to be included less, valued less, and less safe than those without learning disability. Staff also reported having less confidence, capability and capacity to meet the needs of this population compared to those without learning disability. Whilst learning disability nurse provision may impact staff capability to care for children and young people with learning disability, this was not the case in terms of their capacity or confidence or how children and young people are valued within the hospital, their safety and access to appointments. Our study suggests that children and young people with learning disabilities may be invisible, unheard and disadvantaged with respect to receiving individualised high-quality hospital care that meets their needs. In order to deliver continuous high-quality care further in-depth research is needed to understand: the experience of this population; the ability of staff to meet their needs; the impact of the learning disability nurse.